Water Supply Treatment Sustainability of Panching Water Supply Treatment Process - Water Footprint Approach - Aziz E.A.; Malek M.A.; Moni S.N.; Zulkifli N.F.; Hadi I.H. (Institute of Physics Publishing, 2023)
Land use; Sustainable development; Water supply; Treatment process; Water consumption; Water demand; Water footprint; Water intakes; Water treatment